Rickety Stitch and the gelatinous goo. The middle-route run - Costa, Ben, 1984-; Parks, James (Alfred A. Knopf, 2018)
Continuing the quest to discover his true origin, Rickety Stitch and his sidekick, Goo, must find the kingdom of Epoli. But to reach the legendary kingdom, they must contend with the dangerous road of bandits and monsters called the Middle-Route Run.